P794 Effectiveness of administering zinc acetate hydrate to patients with inflammatory bowel disease and zinc deficiency: a retrospective observational two-center study. (30th January 2023) - Sakurai, K; Katsurada, T; Aoyama, K; Fukushima, S; Onishi, R; Yagisawa, K; Nishimura, H; Ito, T; Furukawa, S; Maemoto, A; Sakamoto, N
Abstract: Background: Inflammatory bowel disease (IBD) patients frequently have zinc deficiency and that IBD patients with zinc deficiency are at higher risk for IBD-related complications and surgery. We reported the efficacy of zinc replacement therapy for IBD patients with zinc deficiency at ECCO2020, and now we report the results of our analysis with an extended observation period and an additional number of patients. Methods: IBD patients with zinc deficiency who received zinc acetate hydrate (ZAH) from March 2017 to November 2021 were registered in this 2-center（Hokkaido University Hospital and Sapporo Higashi Tokushukai Hospital）, retrospective, observational study. Results: One hundred twenty patients with Crohn's disease (CD, n=82) or ulcerative colitis (UC, n=38) were registered. Median serum zinc level and CDAI in CD patients significantly improved (59.0-92.3 μg/dL, P<0.001; 118-86, P<0.001, respectively) 4 weeks after ZAH administration. Similarly, median serum zinc levels and CDAI significantly improved (58.5-82.0 μg/dL, P<0.001; 96-78, P<0.001, respectively) 20 weeks after ZAH administration. In the 18 patients who underwent endoscopy both within 4 weeks before and within 60 weeks after ZAH administration, median SES-CD improved from 11.5 to 5.5 (P<0.001). Logistic regression analysis identified "serum zinc level ≥52 μg/dl before ZAH administration" as a factor contributing to normalization of serum zinc concentration and "CDAI ≥96 before ZAH administration" as a factor contributing to improvement of disease activity. Median serum zinc level and partial Mayo scores (PMS) in UC patients significantly improved (63.0-94.0μg/dL, P<0.001; 2-0, P=0.002, respectively) 4 weeks after ZAH administration. Median serum zinc levels significantly improved (62.0-100.0μg/dL, P<0.001) 20 weeks after ZAH administration, but no significant changes in PMS were observed. In the 12 patients who underwent endoscopy both within 4 weeks before and within 60 weeks after ZAH administration, median UCEIS improved from 5 to 3 (P=0.004). Logistic regression analysis identified "dose of ZAH ≥75 mg/day" as a factor contributing to normalization of serum zinc concentration and "serum zinc level ≥65 μg/dl before ZAH administration" as a factor contributing to improvement of disease activity. In both CD and UC, there was a significant correlation between serum zinc level and CDAI, CRP, and serum albumin level before ZAH administration. Conclusion: ZAH administration to IBD patients with zinc deficiency is effective in improving zinc deficiency and may contribute to improving disease activity in IBD.